Fgf8/18 antagonizes Shh expression in lingual ventral–dorsal patterning - Yang, Shuhui; Xue, Junyuan; Liu, Han; Zhou, Nan; Feng, Hui; Li, Nan; Liu, Bo; Zhu, Lei; Xiao, Jing; Liu, Chao (Frontiers in Cell and Developmental Biology, 2026)
IntroductionThe cellular and molecular mechanisms in tongue development are still poorly understood. Explicating how the developing tongue is patterned into a dorsally wide and ventrally narrow asymmetry would benefit the pathological interpretation of tongue deformities.MethodsIn this study, we first revealed that the dorsal extension of Fgf8 from the ventral mesenchyme in Osr2-creKI;Rosa26R-Fgf8 mouse embryonic tongues disrupted dorsal–ventral asymmetry by suppressing the cell proliferation and tenogenic differentiation of lingual dorsal mesenchyme. By intersecting the differentially expressed genes (DEGs) in mouse embryonic dorsal tongues with the canonical gene set of dorsal–ventral pattern formation, Shh and Shh-related genes were found to be specifically activated in the embryonic dorsal tongue. The DEGs between WT dorsal and Osr2-creKI;Rosa26R-Fgf8 dorsal tongues showed that the expression of Lhx6, an Fgf8/18-related transcription factor robustly expressed in the WT ventral tongue, was increased in the Osr2-creKI;Rosa26R-Fgf8 dorsal tongue.ResultsHistological assays verified that in both Osr2-creKI;Rosa26R-Fgf8 and Shh-cre;Rosa26R-Fgf8 embryonic tongues, the expression of Shh and Shh-related genes, including goosecoid (Gsc), Foxa2, and Foxf1, was suppressed in the dorsal area, while the transcription of the ventrally located Fgf8/18-related Lhx6 was extended into the dorsal area. FGF8 or FGF18 supplementation in WT tongues recapitulated the suppression of Shh and Shh-related genes. However, exogenous SHH neither suppressed Fgf18 and Lhx6 nor activated the Shh-related gene Foxf1 in the lingual ventral mesenchyme. These results indicate the involvement of Shh and Fgf8/18 in lingual dorsal–ventral patterning, in which ventral Fgf8/18 suppresses the extension of dorsal Shh.DiscussionOur findings not only confirm the existence of dorsal–ventral patterning during tongue development but also identify Shh and Fgf8/18 as key genes defining the lingual dorsal–ventral axis, providing cellular and molecular clues for interpreting the clinical manifestations of congenital lingual deformities.